Discovery and biosynthesis of specialized metabolites produced by an indigenous streptomyces strain - Candra, Hartono (Nanyang Technological University, 2022)
Microbial natural product discovery was revitalized in recent years driven by the discovery of cryptic secondary metabolite biosynthetic pathways. For my Ph.D. study, I focused on the quarry lake-dwelling Streptomyces tasikensis P46 strain for natural product discovery. My research led to the discovery of tasikamides A-G, a novel family of non-ribosomal peptides that share a unique pentapeptide scaffold. A surprising hydrazone group was found in tasikamides A-C that joins the cyclic peptide scaffold to an alkyl 5-hydroxyanthranilate (AHA) moiety. We discovered that the biosynthesis of tasikamides A-C involves two pathways that produce the cyclic peptide scaffold and the AHA moiety, respectively. We elucidated a novel mechanism whereby tasikamides A-C are biosynthesized via pathway coupling and an unprecedented in vivo Japp-Klingemann reaction. Besides tasikamides, I also discovered a new polyketide-terpenoid hybrid natural product (furaquinocin K) and proposed a novel regulatory mechanism that involves the deamination of an intermediate via diazotization.